Pengaruh Batang Bawah dan Jenis Tunas pada Mikrografting Manggis (Garcinia mangostana) secara In Vitro - Handayani, Rd. Selvy; Poerwanto, Roedhy; Sobir, ,; Purwito, Agus; Ermayanti, Tri Muji (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
The aim of this study was to investigate the effect of rootstock and shoot types on in vitro mangosteen micrografting.The experiment was arranged in completely randomized design (CRD) with two factors. The first factor was the rootstocktype, i.e. rooted planlet from the germination of quartered seed, and rooted planlet from the germination of undivided seeds.The second factor was the developmental phase of scion, i.e. dormant buds, and flush (had new leaf more than 2-4 mm). Theresults showed that rootstock derived from the germination of undivided seed had a higher success rate than other treatmentson all variables, except for number of new leaves. The use of flush as scion was better than dormant buds; flush resulted in ahigher percentage of successful micrograft and longer shoots. In vitro micrografting had a better growth rate than grafting at the same age. The results of anatomical observation conducted at four months after micrografting demonstrated that there was a good graft union, indicated by excellent fusion between rootstock and scion xylem tissues.Keywords: flush, in vitro, micrografting, rootstock, scion